2011
DOI: 10.1111/j.1600-0668.2011.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radical yields from reactions of terpene mixtures with ozone

Abstract: The data presented here demonstrate that mixtures may react differently than the sum of their individual components. By investigating the chemistry of mixtures of chemicals in contrast to the chemistry of individual compounds, a better assessment can be made of the overall impact cleaning products have on indoor environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…These terpenes are typically detectable in herbs, spices, flowers, and plants (Rohr, 2013). For this reason, these chemicals are frequently used as fragrances in commercial air fresheners used indoors (Forester and Wells, 2011), and their amount in air fresheners varies from 0.2-26% (Nazaroff et al, 2006). Terpene concentration in indoor air is associated with temperature.…”
Section: Terpenes (D-limonene)mentioning
confidence: 99%
See 2 more Smart Citations
“…These terpenes are typically detectable in herbs, spices, flowers, and plants (Rohr, 2013). For this reason, these chemicals are frequently used as fragrances in commercial air fresheners used indoors (Forester and Wells, 2011), and their amount in air fresheners varies from 0.2-26% (Nazaroff et al, 2006). Terpene concentration in indoor air is associated with temperature.…”
Section: Terpenes (D-limonene)mentioning
confidence: 99%
“…OH can react with NO, alkanes, alkenes, alcohols, and aromatic compound as well as monoterpene Laumbach and Kipen, 2010). Chamber studies determined OH formation in the reactions between ozone and a single terpene, two-component terpene mixtures (Forester and Wells, 2011).…”
Section: Formation Of Oxidation Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should also be noted that the reaction between alkenes and ozone generates not only sCI but also OH at significant yields (e.g., the OH yield for the reaction of α-pinene and O 3 is ca. 0.77; Forester and Wells, 2011) and that the OH produced via this mechanism is taken into account by Eq. (4).…”
Section: Calculated Ohmentioning
confidence: 99%
“…O 3 can react with isoprene and others terpenes to give corresponding carbonyls [491]. It was also shown that ozonolysis of terpenes as -terpineol, limonene, and -pinene is associated with formation of HO • , reaction (58) [492].…”
Section: Ozone Omentioning
confidence: 97%